Maternal Vitamin B12 Status and Risk of Cleft Lip and Cleft Palate Birth Defects in Tamil Nadu State, India. (May 2021) - Munger, Ronald G.; Kuppuswamy, Rajarajeswari; Murthy, Jyotsna; Balakrishnan, Kalpana; Thangavel, Gurusamy; Sambandam, Sankar; Kurpad, Anura V.; Molloy, Anne M.; Ueland, Per M.; Mossey, Peter A.
Background and Objective: The causal role of maternal nutrition in orofacial clefts is uncertain. We tested hypotheses that low maternal vitamin B12 and low folate status are each associated with an increased risk of isolated cleft lip with or without cleft palate (CL±P) in a case–control study in Tamil Nadu state, India. Methods: Case-mothers of CL±P children (n = 47) and control-mothers of unaffected children (n = 50) were recruited an average of 1.4 years after birth of the index child and plasma vitamin B12, methylmalonic acid (MMA), total homocysteine (tHcy), and folate were measured at that time. Logistic regression analyses estimated associations between nutrient biomarkers and case–control status. Results: Odds ratios (ORs) contrasting biomarker levels showed associations between case-mothers and low versus high plasma vitamin B12 (OR = 2.48, 95% CI, 1.02-6.01) and high versus low plasma MMA, an indicator of poor B12 status (OR = 3.65 95% CI, 1.21-11.05). Case–control status was not consistently associated with folate or tHcy levels. Low vitamin B12 status, when defined by a combination of both plasma vitamin B12 and MMA levels, had an even stronger association with case-mothers (OR = 6.54, 95% CI, 1.33-32.09). Conclusions: Mothers of CL±P children in southern India were 6.5 times more likely to have poor vitamin B12 status, defined by multiple biomarkers, compared to control-mothers. Further studies in populations with diverse nutritional backgrounds are required to determine whether poor maternal vitamin B12 or folate levels or their interactions are causally related to CL±P.